Splicing factor mutations in the myelodysplastic syndromes: target genes and therapeutic approaches. (January 2018) - Armstrong, Richard N.; Steeples, Violetta; Singh, Shalini; Sanchi, Andrea; Boultwood, Jacqueline; Pellagatti, Andrea
Abstract: Mutations in splicing factor genes ( SF3B1, SRSF2, U2AF1 and ZRSR2 ) are frequently found in patients with myelodysplastic syndromes (MDS), suggesting that aberrant spliceosome function plays a key role in the pathogenesis of MDS. Splicing factor mutations have been shown to result in aberrant splicing of many downstream target genes. Recent functional studies have begun to characterize the splicing dysfunction in MDS, identifying some key aberrantly spliced genes that are implicated in disease pathophysiology. These findings have led to the development of therapeutic strategies using splicing-modulating agents and rapid progress is being made in this field. Splicing inhibitors are promising agents that exploit the preferential sensitivity of splicing factor-mutant cells to these compounds. Here, we review the known target genes associated with splicing factor mutations in MDS, and discuss the potential of splicing-modulating therapies for these disorders.